Mechanical and wear properties of Mo5Si3–Mo3Si–Al2O3 composites. (June 2017) - Chen, H.; Shao, X.; Wang, C.Z.; Pu, X.P.; Zhao, X.C.; Huang, B.X.; Ma, J.
Abstract: Mo5 Si3 and Mo5 Si3 –Mo3 Si–Al2 O3 composite were synthesized use MoO3, Mo, Si and Al as raw materials by mechanically induced self propagating reaction and then consolidated by hot-pressing. The microstructure of the materials was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) with X-ray energy dispersive spectroscopy (EDS). The effects of the Al2 O3 on the mechanical and tribological properties of Mo5 Si3 –Mo3 Si–Al2 O3 composite have been studied. It was found that benefits associated with the addition of the Al2 O3 to Mo5 Si3 and Mo3 Si include finer microstructure, higher strength, higher fracture toughness and higher hardness. The dry sliding wear properties of the composite were investigated using against GCr15 bearing steel in ball-on-disk system at room temperature. The results indicated that the friction coefficients and specific wear rates of Mo5 Si3 –Mo3 Si–Al2 O3 composite were significantly reduced by the addition of Al2 O3, and its specific wear rates decreased by an order of magnitude compare with the monophase Mo5 Si3 . The friction coefficients of test materials decrease with an increasing load. The dominant wear mechanism of the composites was interpreted by several different wear models involving plastic deformation, adhesion, brittle fracture and reaction to form a tribo-oxidation layer. Highlights: Mechanical and tribological properties of Mo5 Si3 –Mo3 Si–Al2 O3 composite were studied. The addition of Al2 O3 to Mo5 Si3 could effectively improves its mechanical properties. The composite have an excellent wear resistance compared to the monophase Mo5 Si3 . The friction coefficients of test materials decrease with an increasing load. Wear mechanism of the composites was interpreted by several different wear models.